Young children's play practices with digital tablets : playful literacies - Fróes, Isabel (Emerald Publishing Limited, 2019)
The ebook version of this title is Open Access, thanks to Knowledge Unlatched funding, and is freely available to read online.This book presents how young children's current practices when playing with tablets inform digital experiences in Denmark and Japan. Through an interdisciplinary lens and a grounded theory approach, Fróes identifies and maps these practices, which compose the taxonomy of tablet play and proposes a series of theoretical concepts that complement recent theories related to play and digital literacy studies. Tablet devices bring with them not only a multitude of options, but they also help create notions of digital space and environments defining emerging territories in young children's play experiences. Young children play with these devices and have fun indulging in digital worlds, while discovering and problem-solving with a variety of narratives and interfaces encountered on these digital playgrounds. A set of tablet play characteristics, such as multimodal applications (apps) combined with tablets' physical and digital affordances shape children's digital play.The data collected through observations informed some noteworthy aspects, including how children's hands gain and perform an embodied knowledge of digital spaces. This embodied knowledge develops through digital play interactions, defining what is proposed as digital penmanship. Complementary to the penmanship, several symbols and a range of modes of use shape a rich multimodal semiotic vocabulary in children's digital play experiences. These early digital experiences set the rules for the playgrounds and assert digital tablets as twenty-first-century toys, shaping young children's playful literacy.